P127 Copd And The Workplace; Attitudes Of Those With And Without The Condition In A Population Based Study. (10th November 2014) - Fishwick, D; Lewis, L; Darby, A; Waterhouse, JC; Wiggans, R; Bradshaw, LM
Abstract : Background: Current estimates support 15% of the total population burden of chronic obstructive pulmonary disease (COPD) to be associated with harmful inhaled occupational exposures. Despite a now substantial body of evidence relating to causation, remarkably little is known about the consequences of these inhaled exposures at an individual level, and the attitudes of workers with and without COPD to these issues. Aim: The aim of this work was to explore attitudes to workplaces, and to other aspects of the management of long-term respiratory problems, from individuals within a large population study with and without COPD. Methods: The primary aim of this population-based study was to assess the contribution made by inhaled occupational exposures to the development of COPD. The study was based in Sheffield, historically an industrialised part of the UK. A sub sample of cases of self reported COPD (n = 66) and non cases of COPD (n = 224) were asked to rate their views to a set of 36 pre defined statements, each rated between "don't agree" and "completely agree" on a five point scale. Statements included enquiry about attitudes to chronic respiratory ill health, smoking, general health issues and the influences of the workplace on health. Results: 290 individuals, all 55 years old or greater, participated, 172 (59%) of whom were male. The majority of participants generally agreed or completely agreed with most statements, although various differences emerged between those with and without COPD. For example, those with self reported COPD were more likely, as anticipated, to identify this condition as a longer term health problem, but less likely to agree that workers with possible breathing problems should talk to their employer about these or undergo regular spirometry to identify these. Conclusions: This study has identified a set of attitudes and beliefs from those with and without COPD relating to chronic respiratory problems at work. Knowledge of these semi-quantitative data will assist the development of better workplace interventions to reduce the burden of this condition.